Revisiting Provider Role in Patient Use of Online Medical Records - Mukhopadhyay, Surma; Basak, Ramsankar; Khairat, Saif; Carney, Timothy J. (Applied Clinical Informatics, 2021)
Objectives Provider encouragement for patient use of online medical record (OMR) systems is poorly understood. The study examines temporal trends and predictors of provider encouragement and the effects of encouragement on OMR use.Methods Health Information National Trends Survey administered in 2017 and 2020 were used. Subjects were 18 to 75 years old with access to the Internet or smart devices. From 2017 and 2020, 2,558 and 3,058 subjects were included, respectively.Results In 2020, 52.8% reported receiving provider encouragement within the last year for OMR use compared with 41.3% in 2017 (p < 0.001). For respondents with chronic diseases (such as diabetes, hypertension, heart, or lung diseases [CVMD]), encouragement increased from 45.5 to 57.2% (p < 0.001). Sociodemographic determinants and clinical attributes (e.g., provider office visits, cancer history, or CVMDs) significantly (p < 0.05) predicted encouragement. Among CVMD subjects, gender and visit frequency were significant predictors. OMR use within a year grew recently (73.3% in 2020 vs. 60.6% in 2017, p = 0.002) among CVMD subjects reporting encouragement. Provider encouragement was associated (p < 0.05) with secure communication and viewing results using OMRs controlling for other predictors in the overall cohort and among CVMD subjects.Conclusion Many respondents reported not receiving provider encouragement for OMR use. These subjects represent millions of U.S. adults, including those participating during the pandemic, with CVMDs or cancer history. Encouragement rates grew over time and was associated with demographic or disease attributes and with OMR use. Future research should assess the optimality of encouragement. Resources enabling provider encouragement should continue and help prevent disparity in health technology use.
Keywords: physician; online medical records; patient portal; facilitators and barriers; disparity; public health; health policy